PATIENT SAFETY CULTURE IN HOSPITALS: A LITERATURE REVIEW ON THE IMPLEMENTATION OF SAFETY STANDARDS, ACCOUNTABILITY, AND LEGAL PROTECTION FOR PATIENTS AND MEDICAL PERSONNEL - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (Adisam Publisher, 2025)
Patient safety culture in hospitals is a very important aspect in ensuring the quality and safety of health services. This study is a literature review that aims to analyse the implementation of patient safety standards, the responsibilities of hospitals and medical personnel, and legal protection for patients and medical personnel. Data was obtained through a review of literature from scientific journals, books, and relevant laws and regulations. The results of the study show that the implementation of safety standards such as patient identification, effective communication, safe use of medicines, infection prevention, and fall risk management still faces various obstacles, including organisational culture and resource constraints. In addition, legal responsibility for hospitals and medical personnel is crucial in maintaining fairness and professionalism, while adequate legal protection is a prerequisite for creating a safe working environment and supporting incident reporting. This study emphasises that the synergy between the implementation of standards, legal responsibility, and legal protection is the main foundation for building a sustainable patient safety culture. These findings can be used as a basis for further policy development and empirical research in the context of healthcare in Indonesia and other countries.